Extensive gene flow among populations of the cavernicolous shrimp at the northernmost distribution margin in the Ryukyu Islands, Japan. Issue 10 (14th October 2020) - Yorisue, Takefumi; Iguchi, Akira; Yasuda, Nina; Mizuyama, Masaru; Yoshioka, Yuki; Miyagi, Aika; Fujita, Yoshihisa
Abstract : Marine cave habitats in the Ryukyu Islands, Indo-West Pacific, are located at the northern edge of the distribution of many cave-dwelling species. At distribution margins, gene flow is often more restricted than that among core populations due to the smaller effective population size. Here, we used high-throughput sequencing technology to investigate the gene flow pattern among three sampling sites of a marine cave-dwelling species at the margin of its distribution range. We collected individuals of the barbouriid shrimp Parhippolyte misticia from three marine caves in the Ryukyu Islands and performed population genetic analyses by means of multiplexed inter-simple sequence repeat genotyping by sequencing. Based on 62 single-nucleotide polymorphism markers, no clear population structure or directional gene flow pattern was found among the three sites. These results were unexpected because previous studies of other stygobitic shrimps in this region did find significant population genetic structures and northward directional gene flow patterns . Together, these inconsistent findings imply that marine cave-dwelling species in the region have different mechanisms of larval dispersal. Future studies on larval ecology and the biotic and abiotic factors influencing gene flow patterns are needed to clarify the mechanisms underlying the population dynamics of marine cave-dwelling species.